Heat Adaptation and Nutrition Practices: Athlete and Practitioner Knowledge and Use - Alabdulwahed, S.; Galán-Lopez, N.; Hill, T.; James, L. J.; Chrismas, B. C. R.; Racinais, S.; Stellingwerff, T.; Leal, D. V.; Hausen, M.; CHamari, K.; Fullagar, H. H. K.; Esh, C.; et al. (International Journal of Sports Physiology and Performance, 2022)
Purpose: To survey elite athletes and practitioners to identify (1) knowledge and application of heat acclimation/acclimatization (HA) interventions, (2) barriers to HA application, and (3) nutritional practices supporting HA. Methods: Elite athletes (n = 55) and practitioners (n = 99) completed an online survey. Mann-Whitney U tests (effect size [ES; r]) assessed differences between ROLE (athletes vs practitioners) and CLIMATE (hot vs temperate). Logistic regression and Pearson chi-square (ES Phi [?]) assessed relationships. Results: Practitioners were more likely to report measuring athletes` core temperature (training: practitioners 40% [athletes 15%]; P = .001, odds ratio = 4.0, 95% CI, 2%-9%; competition: practitioners 25% [athletes 9%]; P = .020, odds ratio = 3.4, 95% CI, 1%-10%). Practitioners (55% [15% athletes]) were more likely to perceive rectal as the gold standard core temperature measurement site (P = .013, ? = .49, medium ES). Temperate (57% [22% hot]) CLIMATE dwellers ranked active HA effectiveness higher (P < .001, r = .30, medium ES). Practitioners commonly identified athletes` preference (48%), accessibility, and cost (both 47%) as barriers to HA. Increasing carbohydrate intake when training in the heat was more likely recommended by practitioners (49%) than adopted by athletes (26%; P = .006, 95% CI, 0.1%-1%). Practitioners (56% [28% athletes]) were more likely to plan athletes` daily fluid strategies, adopting a preplanned approach (P = .001; 95% CI, 0.1%-1%). Conclusions: Practitioners, and to a greater extent athletes, lacked self-reported key HA knowledge (eg, core temperature assessment/monitoring methods) yet demonstrated comparatively more appropriate nutritional practices (eg, hydration).